Magistrates’ Travelling Libraries: The Circulation of Normative Knowledge in the Portuguese Empire of the Late 18th Century - Airton Ribeiro da Silva Jr. (Rechtsgeschichte - Legal History)
The pluricontinental Portuguese judicial administration was characterized by intensive movement of personnel around and between its dominions, forming a global network of rotating judicial posts. Along with these individuals, their books circulated, too. The present study focuses on the lists of books of eleven magistrates appointed to judicial posts in a range of locations throughout Portuguese America between 1799 and 1807. Censorship sources allow us to identify the books chosen by these itinerant magistrates as being indispensable for the exercise of their judicial function. In view of the cost of shipping, the books’ weight and, above all, the temporary character of the functionaries’ posts, judges established travelling libraries, portable collections of essential professional books. Identifying the books selected by judges as the work tools for their overseas judicial activities provides a good idea of the legal literature available in the ﬁnal years of the Portuguese Ancien Régime. Finally, this investigation sheds light on how – and what kind of – normative information circulated in Portugal’s colonies along with these agents of the Crown.